Pentingnya Transmisi Nilai Founder pada Family Business Bidang Kesehatan - Catherine Marcia Irawan; Metta Padmalia; Andrea Gideon (Journal of Economics and Management Scienties, 2026)
Family business research generally focuses on succession issues, while the transmission of founder values—particularly in the healthcare context—remains relatively underexplored, despite the intuition that healthcare relies heavily on trust, clinical-patient ethics, and professionalism. Organizational culture serves as a mechanism for institutionalizing founder values, maintaining consistency of service identity, professional quality, and patient trust across generations, and enabling organizational intentions to occur without the founder's direct involvement. This study aims to explore how organizational culture/founder values ​​are constructed, transmitted, and interpreted across generations in a healthcare family business. The study employs a social constructivism paradigm with a qualitative case study approach. Data were collected through semi-structured interviews with the founder, successor, second-born child, and senior manager, and analyzed using open-axial-selective coding and reflexive thematic analysis. The findings identify three core values—compassion, integrity, and excellence—that manifest interconnectedly in the clinical, business, and leadership domains. These values ​​are not mechanically replicated but rather reproduced and reinterpreted according to generational roles and contexts, ultimately becoming institutionalized as organizational culture. This process allows the organization to maintain its service identity, professional quality, and patient trust, even as the founder begins to withdraw from direct involvement.